SECONDARY METABOLITE FROM ENDOPHYTIC FUNGI Aspergillus niger OF THE STEM BARK OF KANDIS GAJAH (Garcinia griffithii) - Elfita Elfita; Muharni Muharni; Munawar Munawar; Septa Aryani (Universitas Gadjah Mada, 2012)
Garcinia griffithii are known as kandis gajah including the Garcinia genus. This plant has been traditionally used by local communities Sarasah Bonta, Lembah Arau, West Sumatra, to treat various diseases including gout. Aspergillus niger was isolated from the tissues of the stem bark of Garcinia griffithii. The fungi strain was identified base on colony and cell morphology characteristic. Aspergillus niger cultured in media 5L Potatos Dextose Broth (PDB) for 8 weeks and filtered. Media that already contains secondary metabolites are partitioned using ethyl acetate solvent in 5 L (twice), followed by evaporation. Furthermore, the extract is separated by chromatographic techniques to obtain a pure compound of white crystal. The molecular structures of isolated compounds are determined by spectroscopic methods including IR, 1H-NMR, 13C-NMR, HMQC, HMBC, and COSY. The compound was determined as phenolic (1).